2009
DOI: 10.7326/0003-4819-151-8-200910200-00006
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Meta-analysis: Associations of 150 Candidate Genes With Osteoporosis and Osteoporotic Fracture

Abstract: Requests for Single Reprints:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
181
1
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(196 citation statements)
references
References 63 publications
8
181
1
6
Order By: Relevance
“…Although none of these SNPs remained significantly associated with LS BMD a after correcting for multiple testing, some of them have been associated previously with LS BMD a in GWAS at genome-wide significant levels, including rs9594738 located approximately 200 kb upstream of RANKL (36) and rs3134057, rs3134058, and rs2073618 within OPG. (43) In addition, rs3134057 and rs3134058 were associated with LS BMD a in the whole-genome study of Styrkarsdottir and colleagues, but not at a genome-wide significance level. (36) Previous candidate gene association studies also have reported an association between rs2073618 and LS BMD a .…”
Section: Discussionmentioning
confidence: 95%
“…Although none of these SNPs remained significantly associated with LS BMD a after correcting for multiple testing, some of them have been associated previously with LS BMD a in GWAS at genome-wide significant levels, including rs9594738 located approximately 200 kb upstream of RANKL (36) and rs3134057, rs3134058, and rs2073618 within OPG. (43) In addition, rs3134057 and rs3134058 were associated with LS BMD a in the whole-genome study of Styrkarsdottir and colleagues, but not at a genome-wide significance level. (36) Previous candidate gene association studies also have reported an association between rs2073618 and LS BMD a .…”
Section: Discussionmentioning
confidence: 95%
“…Thus, a genome-wide search offers advantages over candidate gene association studies because it provides a more extensive coverage of the genome and the opportunity for truly novel gene discoveries-which is entirely "agnostic" and unconstrained by existing knowledge. In fact, many candidate genes, even if validated by the replication of several studies, were not confirmed by GWAS results (Richards et al 2009). Recent reports from GWAS demonstrate the potential of this approach to identify novel gene associations for common complex conditions.…”
Section: Gwas Approach For Aging Genes Discoverymentioning
confidence: 99%
“…Studies of rarer variants require much more powerful designs. Both new discovery by GWAS and replication of association findings, especially for complex quantitative phenotypes, require large sample sizes; therefore, multiple consortia, such as GIANT ), GEFOS (Richards et al 2009;), CHARGE (Psaty et al 2009), SunLight (Wang et al 2010), and others, were formed.…”
Section: Gwas Approach For Aging Genes Discoverymentioning
confidence: 99%
“…These SNPs have not yet been reported to be associated with bone density in previous GWAS. [29][30][31] Two of them, on 15q14-15 and 22q11, are located in genes that are known to be expressed in skeletal muscle: 32,33 GLUT 11 encoded by SLC2A11 on 22q11 and RYR3 on 15q14-15. Because muscle contraction has a major impact on bone density, this might represent an indirect role of these genes on bone density.…”
Section: Simulation Studymentioning
confidence: 99%